Changes in substance use among adolescents before and during the COVID-19 pandemic in Guatemala - Monzon, Jose; Barnoya, Joaquin; Mus, Sophia; Davila, Gustavo; Vidaña-Pérez, Desirée; Thrasher, James F. (Frontiers in Psychiatry, 2024)
Objectives: Due to the COVID-19 pandemic, on March 16 th , schools had to be closed in Guatemala and went to online teaching. We sought to analyze the change in substance use among high school students in Guatemala associated with the lockdown. Methods: Data from two surveys (2019, n=2096, and 2020, n=1606) of a student cohort in private high schools in Guatemala City was used. Logistic models for past 30-day cigarette, e-cigarette, marijuana, and alcohol (including binge drinking) were used, regressing these on survey wave, while adjusting for sex, scholastic performance, high school year of student, parental education, substance use, and household member tobacco use.Results: Prevalence declined for smoking (10% to 3%, p<0.001), e-cigarette (31% to 14%, p<0.001), marijuana (4.3% to 1.9%, p<0.001), and alcohol use (47% to 38.5%, p<0.001), and binge drinking (24% to 13%, p<0.001). Adjusted models showed wave 2 associated with lower odds of using cigarettes (AOR=0.44, 95%CI=0.32-0.62), ecigarettes (AOR=0.41, 95% CI=0.35-0.49, p<0.001), and binge drinking (AOR=0.73, 95%CI=0.59-0.89; p=0.002) Conclusion: Among Guatemalan adolescents, COVID-19 restrictions were associated with a significant decrease in smoking, e-cigarette use, and binge drinking.